2012
DOI: 10.1016/j.celrep.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A Resource for Manipulating Gene Expression and Analyzing cis-Regulatory Modules in the Drosophila CNS

Abstract: Here we describe the embryonic CNS expression of 5,000 GAL4 lines made using molecularly defined cis-regulatory DNA inserted into a single attP genomic location. We document and annotate the patterns in early embryos when neurogenesis is at its peak, and in older embryos where there is maximal neuronal diversity and the first neural circuits are established. We note expression in other tissues such as the lateral body wall (muscle, sensory neurons, trachea) and viscera. Companion papers report on the adult bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 60 publications
1
106
0
Order By: Relevance
“…iCasper can also be used to examine spatiotemporal dynamics of apoptosis in a number of diseases including cancer. Moreover, iCasper may be used to study apoptosis in cell-typespecific lineage tracing during normal and disease development when combined with the large number of recently developed GAL4 lines (30)(31)(32). iCasper will also be useful to dissect signaling networks that lead to apoptosis by high-throughput screening using cultured cells or small animals.…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%
See 1 more Smart Citation
“…iCasper can also be used to examine spatiotemporal dynamics of apoptosis in a number of diseases including cancer. Moreover, iCasper may be used to study apoptosis in cell-typespecific lineage tracing during normal and disease development when combined with the large number of recently developed GAL4 lines (30)(31)(32). iCasper will also be useful to dissect signaling networks that lead to apoptosis by high-throughput screening using cultured cells or small animals.…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%
“…iCasper represents a useful tool for future studies examining molecular mechanisms of cancer, as well as lineage tracing of specific types of cells during normal and tumor development when combined with the large number of recently developed GAL4 lines (30)(31)(32).…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%
“…We chose to add Gal4 lines expressed in 1-10 neurons per hemisegment, which gave us the dual benefit of increasing known molecular markers for interneurons and of providing functional access to these neurons for the first time. From a previous large-scale screen of 5000 Gal4 lines (Manning et al, 2012), we selected 75 lines with strong, regular expression patterns at late embryonic stages. We used each Gal4 line to express a nuclearlocalized GFP, and created a single-marker atlas for each line ( Fig.…”
Section: The Eneuro Atlas: a Single Atlas Containing Eight Transcriptmentioning
confidence: 99%
“…We used standard methods to stain Drosophila embryos (Manning et al, 2012). Primary antibodies were mouse Eve 2B8 (1:50), mouse En 4D9 (1:10), and rat Elav (1:10), all from the Developmental Studies Hybridoma Bank (DSHB) developed under the National Institute of Child Health and Human Development (NICHD) and maintained by the University of Iowa; guinea pig Dimm (1:100; a gift from S. Thor, Linkoping University, Sweden); rat Repo (Campbell et al, 1994) (1:1000); rabbit pMad (pS1 1:300; Peter Ten Dijke, Leiden University Medical Center, Leiden, The Netherlands); chicken GFP (1:1000; Aves, Tigard, OR); rabbit Hb9 (Odden et al, 2002) (1:1000); and guinea pig Fox (Nechipurenko and Broihier, 2012) (1:20).…”
Section: Embryo Immunostaining and Stagingmentioning
confidence: 99%
“…To evaluate the regulatory potential of intronic regions in the fly, we tested ten GAL4 lines with fragments from the InR gene (Pfeiffer et al, 2008). Previous measurements in the embryo indicated that some of these elements drive GFP expression in dynamic patterns (Jenett et al, 2012;Jory et al, 2012;Manning et al, 2012;Li et al, 2014). Three of the fragments also express GFP in larvae and adults, in either ubiquitous or tissue-specific patterns (Fig.…”
Section: Candidate Regulatory Regions In Inr Intronsmentioning
confidence: 99%